Confusion in forest management In the age of regional autonomy - Baso Madiong (Indonesia Prime, 2018)
The forest area, shared at KPH became part of strengthening the management of the national forestry system, provincial governments, and district/city governments. KPH is set in one or more major functions of the forest and one of the administration areas or crosses the territory of the government administration. In that case one can include, kph over the main function of forests, and determine the degree of functionality-based KPH dominance. The organization established by the KPH Governments, encompasses the organizations of KPHK or KPHL and the region it works kph Province, a kph organization set by the provincial government, including organizations and crosses kph KPHL District/City and an organization KPH set by county government / The city, the content of the institution and within Kphp KPHL District / City